Synthesis of L-Lactide-Based Segmented Polyurethanes. (12th June 2016) - Monga, Sheetal; Kaushik, Anupama; Gupta, Bhuvanesh
ABSTRACT: A series of segmented polyurethanes with polylactidediols soft segments and methylene-diphenyl-diisocyanate/1, 4-butanediol hard segments with molecular weights in the range of 6.18 × 10 3 to 9.36 × 10 3 Da were synthesized. Stannous octoate was the catalyst for the reactions. These polymers were characterized using Fourier transform infrared spectroscopy, X-ray diffraction, gel permeation chromatography, and thermogravimetric analyzer. Fourier transform infrared analyses revealed the formation of urethane groups and complete curing of polyurethane. The thermal degradation temperatures were in the range of 248.55–257.09°C. X-ray diffraction studies confirmed the segmented structure of polyurethanes. GRAPHICAL ABSTRACT: